Integrating pharmacovigilance into the routine of pharmacy department: experience of nine years - Ariadna Pérez-Ricart; Elvira Gea-Rodríguez; Ana Roca-Montañana; Esperanza Gil-Máñez; Amanda Pérez-Feliu (Farmacia Hospitalaria)
Objective: To describe our pharmacovigilance program and to analyze the reported adverse drug reactions. Method: Observational longitudinal study conducted from 2008 to 2016. The Pharmacy Department leads the pharmacovigilance program and performs prospective, retrospective, intensive, and spontaneous reporting of inpatients and outpatients (emergencies, day hospital, external consultations, and nursing homes). Each adverse drug reaction is incorporated in the electronic health record of the patient along with an alert. Results: A total of 2,631 adverse drug reactions were reported in 2,436 patients. Of these patients, 52% were men with a mean age of 63.3 [0-98] years. A total of 92.8% drug events were reported by the pharmacists and 7.2% by doctors, nurses, and technicians. A total of 63.7% were reported in inpatients, 19.2% in emergencies, 10.6% in external consultations, 6.2% in the day hospital, and 0.3% in diagnostic radiology. There was an increase in adverse drug reactions detected by prospective and intensive pharmacovigilance. Principal therapeutic groups involved in adverse drug events were antineoplastic agents (21.3%), antibacterials (12.3%), antithrombotics (7.7%), analgesics (6.7%), corticosteroids (5.2%), psycholeptics (5.2%), diuretics (4.9%), antivirals (4.9%), antiinflammatories and antirheumatics (4.2%), and immunosupressants (3.3%). Adverse drug reactions mainly affected the skin and appendages (19.7%) and gastrointestinal tract (19.1%). Adverse drug reactions were mild (38.7%), severe (30.8%), and moderate (30.5%). In total, 60.9% of patients recovered from drug events and 31.7% were in recovery. The most frequent response was reatment interruption in 65% of cases and the patients received additional specific treatment in 56% of cases. Conclusions: The incorporation of the pharmacovigilance program within the daily routine of the hospital pharmacist provides added value to the safety and pharmacotherapy of the patient.